PENGARUH MODEL CIRC BERBANTUAN MEDIA LET’S READ ASIA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SD - Nurrohmah, Siti; Djuanda, Dadan; Dwija Iswara, Prana (Universitas Negeri Medan, 2024)
Reading comprehension is reading in depth to gain an understanding of the information or message in a reading. there are students who have difficulty in understanding the content of reading. Using the pre-experimental design approach and a one-shot case study methodology, this study intends to ascertain the impact of the CIRC model—with assistance from Let's Read Asia media—on the reading comprehension skills of grade V elementary school pupils. This research was conducted 2 times treatment. The sample was 30 students of class V-A in one of the elementary schools in Bandung City. Two methods of gathering data were employed: observation and post-test. The one-sample t-test was employed in data analysis with the JASP version 0.18.3 application to test the hypothesis. The CIRC model assisted by Let's Read Asia media has an effect on students' reading comprehension skills as seen from the p value = 0.001 <0.05 which indicates the rejection of H0 and the acceptance of H1. The CIRC model assisted by Let's Read Asia media has a significant positive effect on students' reading comprehension ability, because the average value of students' post-test is greater than the KKM (75).